VANETs and Internet of Things (IoT): A Discussion - Shahirah Mohamed Hatim; Shamsul Jamel Elias; Norkhushaini Awang; Mohd Yusof Darus (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Recent advancement of wireless technology and Internet of Things (IoT) have brought a significant development in Vehicular Ad hoc Networks (VANETs). VANET and IoT are the key elements in the current Intelligent Transport System (ITS). Various research on VANET and IoT shows that both have substantial effects in smart transportation system. This paper aims to discuss and illustrate the main challenges and drawbacks; the routing protocols, security and privacy experienced by VANETs respectively. This paper also would like to address the importance of IoT based on VANET in traffic control management system to cope up with the new wireless technology era. Section I of this paper provides a brief explanation on VANETs and IoT, section II discusses the main challenges suffered by VANETs and IoT, section III covers on the existing applications of VANETs and IoT and section IV conclude the views.